Radar imaging with compressed sensing for detecting moving targets behind walls - Huang, L. (2013)
This paper presents an investigation about the performance of behind-the-wall moving targets detection and localization using through-the-wall radar imaging with compressed sensing (CS) and small numbers of sensors and frequency bins. We propose a random sparse array geometry, of which elements can be positioned sparsely and randomly for easy and efficient operation. The performance comparisons show that radar imaging with random sparse sensors produce better result with few number of sensor elements.